New oscillation conditions for nonlinear second order differential equations - Abdalla Salhin, Ambarka; Ummul Khair Salma Din; Rokiah Rozita Ahmad; Mohd Salmi Md Noorani (Penerbit Universiti Kebangsaan Malaysia, 2019)
New oscillation conditions for the nonlinear second order differential equations are presented. These criteria involve the use of integral averaging technique. Theorems created in this study are stated in general form, which complement and lengthen some related results known in the literature. The importance of our results is to show that some of the results from previous researches contain superfluous conditions.